Preaching and cartooning: an exploration of the processes involved in developing a sermon and a newspaper cartoon - C. J. Wepener (Acta Theologica)
This article explores the similarities and differences between the process followed to develop a sermon and that followed to develop a cartoon. It first examines the representation of the jester or clown in some recent publications by homileticians before describing the process of development of a sermon, as proposed by three homiletic sources from namely North America, South Africa and The Netherlands, respectively. The article describes the process followed in the development of a cartoon in a similar way. The article concludes by presenting some observations on the preacher as cartoonist with reference to the process followed in the development of a cartoon. It argues that the cartoonist may currently be viewed as a metaphor for a preacher that could enrich existing images of the preacher such as the clown or jester, especially because of the similarities in the processes for writing/preparing a sermon and drawing a cartoon.